2010
DOI: 10.1111/j.1749-6632.2009.05174.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Lepidium meyenii (Maca)

Abstract: The neuroprotective activity of the plant Lepidium meyenii (Maca) was studied in two experimental models: in vitro and in vivo. Crayfish neurons were pretreated with vehicle or the pentane extract from Maca, subjected to H(2)O(2), and their viability determined microscopically and chemically. A significant concentration-neuroprotective effect relationship was demonstrated. The pentane extract was then administered intravenously to rats prior to and following middle cerebral artery occlusion. While infarct volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 65 publications
0
33
0
4
Order By: Relevance
“…En ratas se observó que el extracto pentánico presenta una potencial aplicación como neuroprotector en ratas con infarto cerebral por oclusión de la arteria cerebral media (60) . En humanos, la maca reduce los puntajes de depresión y ansiedad en varones adultos aparentemente sanos (7) .…”
Section: Efecto De La Maca Sobre Memoria Depresión Y Ansiedadunclassified
“…En ratas se observó que el extracto pentánico presenta una potencial aplicación como neuroprotector en ratas con infarto cerebral por oclusión de la arteria cerebral media (60) . En humanos, la maca reduce los puntajes de depresión y ansiedad en varones adultos aparentemente sanos (7) .…”
Section: Efecto De La Maca Sobre Memoria Depresión Y Ansiedadunclassified
“…Macamides which are lipidsoluble and long-chain, are considered the typical markers for maca, and proved to have several pharmacological properties, such as improving sexual performance and neuroprotective effects (Zheng et al 2000;Pino-Figueroa et al 2010;Vu 2012;Wu et al 2013). In previous experiment, we discovered that maca lipidsoluble extract by petroleum ether extraction could significantly extend the weight-loaded swimming time to exhaustion.…”
Section: Introductionmentioning
confidence: 99%
“…44 In addition, Pino-Figueroa et al recently demonstrated that the lipophilic compounds from maca had potential neuroprotective properties in an in vitro crayfish neuronal cell culture. 45 These findings showed that maca extract prevented ROS damage in the nervous system, thus improving depression.…”
Section: Discussionmentioning
confidence: 77%